The individual influence factors of voluntary turnover among knowledge workers in China: A case study of Huawei - Hua Feng; Mengyin Cao (Journal of Contemporary Eastern Asia, 2017)
"Knowledge worker" is a term used to describe highly educated people whose role in the workforce involves the use of information and knowledge. Knowledge workers are key to the success of a great many organizations. Many Chinese companies find that the voluntary turnover rate among their knowledge workers is high. The purpose of this paper is to explore, from the perspective of knowledge workers and the characteristics peculiar to them, the factors that influence this high voluntary turnover rate. The models used in this paper, that will enable understanding of the characteristics of knowledge workers in China, are the Chinese Personality Assessment Inventory and the Five Factors Model. In the case of Huawei, analysis using these models leads to the conclusion that the main factors that influence the voluntary turnover of knowledge workers in China are: age; gender; degree of extraversion and how open the person is to new experiences; family orientation; and occupation. This study leads to the conclusion that the company should pay closer attention to three groups: female employees who put a high value on their families; employees from non-R&D departments; and younger employees who show a high degree of openness to new experiences.